Conducting water-energy-food nexus studies: what, why, and how - Ebrahim Farmandeh; Shahla Choobchian; Shobeir Karami (Scientific Reports)
Abstract The increasing pressure on resources and the persistent failure to address global malnutrition are evident challenges. A significant contributing factor is the decline in the quality of production resources, particularly water. As a result, many countries and their experts have prioritized the need to balance resource consumption. To address the research gap regarding balanced and optimal resource use, various methodologies have been developed over time, culminating in nexus studies. This study aimed to investigate the what, why, and how of conducting water-energy-food nexus (WEFN) studies. The research employed a sequential mixed-methods approach, integrating content analysis with the Analytical Network Process (ANP). The findings reveal that the objectives of WEFN studies encompass a wide range of interests, which can be systematically categorized into seven principal domains: system sustainability assessment, integration of planning and decision-making processes related to resource consumption, optimization of resource use, management of resource consumption systems, development of theoretical frameworks for the nexus, evaluation of the impacts of resource consumption, and assessment of associated risks. Notably, the results indicate that system sustainability assessment is the most critical reason for conducting WEFN studies. Furthermore, the analysis of WEFN methodologies identified simulation as the most effective technique within the Analytical Hierarchy Process (AHP) framework. In the context of the ANP technique, statistical analysis and simulation emerged as the most important methods. This research advocates for using a diagram to facilitate the selection of the optimal method for conducting a WEFN study.